Rethinking punishment: challenging conventions in research and policy - Lucken, Karol (Routledge, 2017)
Introduction -- Justifying punishment : a moral & economic defense of policy -- Defining punishment : the essential attributes of penal activity -- Measuring punishment : the scope & severity of penal activity -- Evaluating punishment : "what works" and the pursuit of effectiveness -- Prescribing punishment : alternative directions in research & policy --